The The Impact of Interprofessional Collaboration on Referral Time for Patients with Neurological Emergencies: The Impact of Interprofessional Collaboration on Referral Time for Patients with Neurological Emergencies - Handi, Andrew (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Neurological emergencies, such as acute stroke and head trauma, require prompt and accurate treatment to reduce the risk of complications and death. Effective interprofessional collaboration among medical teams can expedite referral times and improve patient outcomes. This study aims to evaluate the impact of interprofessional collaboration on the referral time of patients with neurological emergencies. This study uses a quantitative design with an observational analytic approach. The sample consists of 120 patients referred with neurological emergencies across several hospitals. Data were collected through observations of interprofessional interaction frequency and communication, as well as recording referral times Analysis was performed using correlation tests to identify the impact of interprofessional collaboration on referral time. The results show that effective interprofessional collaboration is associated with shorter referral times. Patients referred by teams with good communication between medical professions had an average referral time 25 minutes faster than those with lower collaboration. Communication barriers, such as differences in professional disciplines and lack of coordination, were found to delay referral times. Effective interprofessional collaboration can reduce referral times for patients with neurological emergencies. Therefore, improving interprofessional teamwork in hospitals is essential to expedite patient management and reduce the risk of complications.